The ‘open’ Venice Charter: Learning from the Multiple Interpretations and Translations of the Charter’s Article 9 - Houbart, Claudine; Dawans, Stéphane (Protection of Cultural Heritage, 2025)
This paper contributes to a research initiative aimed at addressing a significant gap in the historiography of the Venice Charter: its translations. Originally composed in French, the charter underwent subsequent translations into English, Spanish, and Russian shortly after its inception, with the French and English versions serving as the basis for subsequent translations. However, a cursory examination of these versions reveals notable disparities, indicating a departure from Umberto Eco’s notion of translations ‘saying almost the same thing’. These linguistic variations gave rise to diverse interpretations over time and across geographical regions, suggesting that the Venice Charter operated more as an ‘open work’ than a rigidly universal standard. While refraining from direct engagement with the charter’s contemporary relevance, this article delves into the potential significance of examining translations and interpretations, focusing on one of its most contentious sections: Article 9 and, particularly, the concepts of ‘distinctiveness’ and ‘contemporary stamp’. These reflections are contextualized through Umberto Eco‘s insights on the nature of the ‘open work’ and the intricacies of the translation process.